2016
DOI: 10.1186/s40885-016-0055-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase in hypertension – an update

Abstract: Hypertension is a prevalent condition worldwide and is the key risk factor for fatal cardiovascular complications, such as stroke, sudden cardiac death and heart failure. Reduced bioavailability of nitric oxide (NO) in the endothelium is an important precursor for impaired vasodilation and hypertension. In the heart, NO deficiency deteriorates the adverse consequences of pressure-overload and causes cardiac hypertrophy, fibrosis and myocardial infarction which lead to fatal heart failure and sudden cardiac dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 67 publications
1
22
0
1
Order By: Relevance
“…In RAS, Ang I is converted into Ang II by angiotensin-converting enzyme (ACE). When Ang II binds to AT1R in the myocardium, the Ang II-AT1R axis acts as a detrimental effector, causing myocardial cell damage and development of heart failure in the following manner: Development of myocardial hypertrophy and increased production of reactive oxygen free radicals leads to cell mitochondrial damage and myocardial cell apoptosis ( 21 , 24 ); promotion of the expression of proinflammatory transcription factors, nuclear factor-κB and interleukin-6 in cells, which subsequently promotes inflammatory reactions; through the action of NADPH oxidase, ultimately increasing the production of reactive oxygen free radicals, which causes damage to cell mitochondria, myocardial hypertrophy, and myocardial fibrosis and dysfunction ( 25 ); and through the phosphatidylinositol 3-kinase/Akt pathway, wherein Akt phosphorylation is reduced and cardiac hypertrophy and cardiomyocyte autophagy are promoted, leading to heart failure ( 26 ). Strohmenger et al ( 27 ) demonstrated that administration of the Ang II antagonist telmisartan during the port-resuscitation phase in pigs improved myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%
“…In RAS, Ang I is converted into Ang II by angiotensin-converting enzyme (ACE). When Ang II binds to AT1R in the myocardium, the Ang II-AT1R axis acts as a detrimental effector, causing myocardial cell damage and development of heart failure in the following manner: Development of myocardial hypertrophy and increased production of reactive oxygen free radicals leads to cell mitochondrial damage and myocardial cell apoptosis ( 21 , 24 ); promotion of the expression of proinflammatory transcription factors, nuclear factor-κB and interleukin-6 in cells, which subsequently promotes inflammatory reactions; through the action of NADPH oxidase, ultimately increasing the production of reactive oxygen free radicals, which causes damage to cell mitochondria, myocardial hypertrophy, and myocardial fibrosis and dysfunction ( 25 ); and through the phosphatidylinositol 3-kinase/Akt pathway, wherein Akt phosphorylation is reduced and cardiac hypertrophy and cardiomyocyte autophagy are promoted, leading to heart failure ( 26 ). Strohmenger et al ( 27 ) demonstrated that administration of the Ang II antagonist telmisartan during the port-resuscitation phase in pigs improved myocardial contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS bioavailability along with decreased NO production and increased NO consumption have been proposed to contribute to the events underlying endothelial injury. Reduced bioavailability of NO in the endothelium is an important precursor for impaired vasodilation and hypertension [20, 21]. The renal arterial infusion of oxLDL greatly enhanced ischemia/reperfusion-induced ROS and inhibited nitric oxide bioactivity [18].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential mechanism is that calcium may indirectly promote endothelial NO synthase activity and NO-mediated vasodilation, increasing insulin secretion or action. Indeed, endothelial NO synthase expression and activation is defective in hypertensive individuals, and this is believed to contribute to elevated blood pressure (208).…”
Section: Calciummentioning
confidence: 99%